2012
DOI: 10.1093/cid/cis841
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors for Pneumocystis Pneumonia Hospitalizations in HIV Patients

Abstract: This study identifies both climatological and air pollution constituents as independent risk factors for hospitalization of HIV-positive patients with PcP in San Francisco. Thus, the environmental effects on PcP are more likely complex than previously thought. Further studies are needed to understand how these factors exert their effects and to determine if these factors are associated with PcP in other geographic locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 42 publications
1
36
2
2
Order By: Relevance
“…Our results suggest that disproportionate exposures may contribute to LGBT populations experiencing disparate burdens from health conditions such as cancer and asthma (Agénor, 2015; Blosnich et al, 2010, 2013; Boehmer et al, 2012; Cochran and Mays, 2012; Heck and Jacobson, 2006; Landers et al, 2011), which have well-established links to air pollution (Kampa and Castanas, 2008). It is also possible that other health problems with disparate effects on sexual minorities—such as obesity, stress, HIV, and related comorbidities—may be influenced by and/or interact with disproportionate exposures to air pollution in a synergistic manner (Baillie-Hamilton, 2002; Chen et al, 2008; Djawe et al, 2013; Kampa and Castanas, 2008). Clearly, more research that tests for environmental health disparities based on LGBT status is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that disproportionate exposures may contribute to LGBT populations experiencing disparate burdens from health conditions such as cancer and asthma (Agénor, 2015; Blosnich et al, 2010, 2013; Boehmer et al, 2012; Cochran and Mays, 2012; Heck and Jacobson, 2006; Landers et al, 2011), which have well-established links to air pollution (Kampa and Castanas, 2008). It is also possible that other health problems with disparate effects on sexual minorities—such as obesity, stress, HIV, and related comorbidities—may be influenced by and/or interact with disproportionate exposures to air pollution in a synergistic manner (Baillie-Hamilton, 2002; Chen et al, 2008; Djawe et al, 2013; Kampa and Castanas, 2008). Clearly, more research that tests for environmental health disparities based on LGBT status is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other health problems with disparate impacts on sexual minorities—such as obesity, stress, HIV and related comorbidities—may be influenced by and/or interact with environmental exposures (Baillie-Hamilton, 2002; Chen et al, 2008; Djawe et al, 2013; Kampa and Castanas, 2008). However, only one extant study, which focused on one US metro area, has investigated disparities in environmental health risks among sexual minorities (Collins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is little direct evidence for the interaction between HIV infection and HAP, a 2013 meta-analysis of 14 observational studies showed that tobacco smoking increases the risk of bacterial pneumonia in patients with HIV, and that smoking cessation is effective to decrease that risk 110. Two studies of the effects of outdoor air pollution on pneumocystis pneumonia showed that exposure to higher temperatures and sulphur dioxide were associated with increased risk of hospital admissions due to pneumocystis pneumonia,111 and that the serological immune response to pneumocystis pneumonia was attenuated by both ambient PM (PM 10 ) and cigarette smoking 112…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…Pneumocystis genotypes and virulence factors [9]); and 3) environmental factors (e.g. climatological factors and air pollutants [10,11]).…”
Section: Introductionmentioning
confidence: 99%
“…The role that specific environmental factors may play in the development of PCP in HIV-positive patients has piqued scientific interest in recent years [1113], because climatological factors and air pollution levels have been shown to have an impact on the progression of several pulmonary diseases [14]. However, published data on environmental factors in relation to PCP disease are somewhat inconsistent.…”
Section: Introductionmentioning
confidence: 99%